Low-temperature thermal conductivity of solid carbon dioxide - Sumarokov, V.V.; Stachowiak, P.; Jezowski, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Preliminary results of the thermal conductivity measurements performed in the temperature range 1.5-35 K on pure carbon dioxide are presented. The data below 25 K have been obtained for the first time. The thermal conductivity coefficient reaches very high value, of about 700 W/(m×K), unusual for simple molecular crystal. Straightforward analysis applied to the data indicates the case of large-grained sample.